"CULTURAL TRADITION OF ECO-NATURE PAINTING OF KISHANGARH": ‘‘किशनगढ़ श्©ली का पर्यावरण-प्रकृति चित्र्ाण की सांस्कृतिक परम्परा’’ - Bhardwaj, Kumkum (International Journal of Research -GRANTHAALAYAH, 2015)
"The paintings of Kishangarh Sh. Of Rajasthan display the awareness of the environment in today’s environment by preserving nature." Vegetation, water, air, three environmental components are depicted in abundance. The cultural tradition of spirituality philosophy is embedded in the environment with nature painting. The picturesque environment of the picturesque environment in the greenery seems to spread the message of saving the environment from getting polluted to the environment, which is a positive effort. Environment refers to the moral and biological system of the entire universe, under which all living beings are. Organisms live in the environment, grow and thrive; Develop their natural tendencies. Man is a part of the environment, apart from that, he has no existence. Air, water, land, vegetation, trees, animals, human beings all make up the environment. "In nature we see something - air, water, soil, vegetation and animals all compose the environment." So ecology is a science of environmental studies. In modern times, since we have renounced spiritual beliefs and science and technology have only accepted the cause of human progress and natural resources. Our environment has become full of crisis for life only when it started burning. 2 This scene of destruction from development has happened due to excessive tapping of nature only. ‘‘राजस्थान की किशनगढ़ श्©ली के चित्र्ा प्रकृति क¨ संरक्षित करके पर्यावरण जागरुकता क¨ आज के परिवेश में प्रदर्शित करते हैं। चित्र्ा¨ं में वनस्पति, जल, वायु तीन¨ं पर्यावरणीय घटक प्रचुर मात्र्ाा में चित्र्ाित हैं। पर्यावरण में प्रकृति चित्र्ाण के साथ अध्यात्म दर्शन की सांस्कृतिक परम्परा क¨ ज¨ड़ा गया है। हरियालीमय सुरम्य वातावरण चित्र्ा¨ं मंे प्रकृति चित्र्ाण की सांस्कृतिक थाती पर्यावरण प्रदूषित ह¨ने से बचाने का सन्देश जन-जन तक पहुँचाती प्रतीत ह¨ती है, ज¨ एक सकारात्मक प्रयास है। पर्यावरण का तात्पर्य समस्त ब्रह्माण्ड के नैतिक एवं जैविक व्यवस्था से है, जिसके अंतर्गत समस्त जीवधारी ह¨ते हैं। पर्यावरण में जीवधारी रहते हैं, बढ़ते हैं अ©र पनपते हैं; अपनी स्वाभाविक प्रवृत्तिय¨ं क¨ विकसित करते हैं। मनुष्य पर्यावरण का ही एक भाग है, उससे पृथक उसका क¨ई भी अस्तित्व नहीं है। वायु, जल, भूमि, वनस्पति, पेड़-प©ध्¨, पशु, मानव सब मिलाकर पर्यावरण बनाते हैं। ‘‘प्रकृति मंे हमें ज¨ कुछ दिखाई देता है- वायु, जल, मिट्टी, वनस्पति तथा प्राणी सभी सम्मिलित रूप से पर्यावरण की रचना करते हैं। अतः पारिस्थितिकी पर्यावरण अध्ययन का एक विज्ञान है।1आधुनिक काल में जब से हमने आध्यात्मिक मान्यताअ¨ं का त्याग किया है तथा विज्ञान अ©र प्र©द्य¨गिकी क¨ ही मानव प्रगति का कारण मान लिया अ©र प्राकृतिक संसाधन¨ं का भरपूर द¨हन करना प्रारंभ किया तभी हमारा पर्यावरण जीवन के लिए संकट पूर्ण ह¨ गया है।2 विकास से विनाश का यह मंजर केवल प्रकृति के अत्यधिक द¨हन के कारण हुआ है।